Prolactin-induced Subcellular Targeting of GLUT1 Glucose Transporter in Living Mammary Epithelial Cells - Riskin, Arieh (Rambam Maimonides Med J, 2015)
BACKGROUND: Studying the biological pathways involved in mammalian milk production during lactation could have many clinical implications. The mammary gland is unique in its requirement for transport of free glucose into the cell for the synthesis of lactose, the primary carbohydrate in milk. OBJECTIVE: To study GLUT1 trafficking and subcellular targeting in living mammary epithelial cells (MEC) in culture. METHODS: Immunocytochemistry was used to study GLUT1 hormonally regulated subcellular targeting in human MEC (HMEC). To study GLUT1 targeting and recycling in living mouse MEC (MMEC) in culture, we constructed fusion proteins of GLUT1 and green fluorescent protein (GFP) and expressed them in CIT3 MMEC. Cells were maintained in growth medium (GM), or exposed to secretion medium (SM), containing prolactin. RESULTS: GLUT1 in HMEC localized primarily to the plasma membrane in GM. After exposure to prolactin for 4 days, GLUT1 was targeted intracellularly and demonstrated a perinuclear distribution, co-localizing with lactose synthetase. The dynamic trafficking of GFP-GLUT1 fusion proteins in CIT3 MMEC suggested a basal constitutive GLUT1 recycling pathway between an intracellular pool and the cell surface that targets most GLUT1 to the plasma membrane in GM. Upon exposure to prolactin in SM, GLUT1 was specifically targeted intracellularly within 90–110 minutes. CONCLUSIONS: Our studies suggest intracellular targeting of GLUT1 to the central vesicular transport system upon exposure to prolactin. The existence of a dynamic prolactin-induced sorting machinery for GLUT1 could be important for transport of free glucose into the Golgi for lactose synthesis during lactation.